Mini Pedal Mesin Basuh Baju - Mohammad Noor, Hafsa; Nor Azman, Muhammad Norhazris; Amran, Nur Syhuhada; Syed Hussin, Sharifah Syafiqah; Kassim, Noraniah; Mat Hassan, Nik Normunira (Multidisciplinary Applied Research and Innovation, 2021)
Doing laundry is an important aspect of personal hygiene. There are two methods of washing clothes, either hand washing or machine washing. In Pagoh Residential College, UTHM there is a problem with the washing machine provided which were unability to serve the numbers of students and the cleanliness is below satisfactory. The washing machines provided in each block is only 3 to accommodate 480 residents, thus students would had a long queue to wash clothes. Therefore, students need equipment that can help washing their clothes easily, quickly and effectively. The Mini Pedal Washing Machine is designed to solve these problems. This product is portable, the time taken to wash clothes is 10 minutes for 2 kg of clothes and help the students who have allergies to laundry detergent. This product is fully manually controlled, using human energy to power the washing cycle and does not require any electrical energy. In short, the product could perform 3 washing techniques, namely washing, rinsing and drying. Testing is performed for the rotation of the tub. With single press on the pedal would translate to 8 rotations of washing. The maximum weight of clothes for one washing cycle is not more than 2 kg. This is to ensure that the clothes can be washed clean and not clumped together during the washing process. With the use of a mini pedal washing machine, the time period is 2 times shorter compared to washing clothes by hand. Students who suffer from allergies would also be greatly benefitted from the lack of needing to scrub their clothes thus limiting contact with the laundry detergent. This product does not use electricity while took the same time as the existing washing machine making it suitable for the use of students in college for daily use.